Exome Sequencing in BRCA1-2 Candidate Familias: The Contribution of Other Cancer Susceptibility Genes - Doddato, Gabriella; Valentino, Floriana; Giliberti, Annarita; Papa, Filomena Tiziana; Tita, Rossella; Bruno, Lucia Pia; Resciniti, Sara; Fallerini, Chiara; Benetti, Elisa; Palmieri, Maria; Mencarelli, Maria Antonietta; Fabbiani, Alessandra; et al. (Frontiers in Oncology, 2021)
Hereditary Breast and Ovarian Cancer (HBOC) syndrome is a condition in which the risk of breast and ovarian cancer is higher than in the general population. The prevalent pathogenesis is attributable to inactivating variants of the BRCA1/2 highly penetrant genes, however, other cancer susceptibility genes may also be involved. By Whole Exome Sequencing (WES) we analyzed a series of 200 individuals selected for genetic testing in BRCA1/2 genes according to the updated National Comprehensive Cancer Network (NCCN) guidelines. Analysis by MLPA was performed to detect large BRCA1/2 deletions/duplications. Focusing on BRCA1/2 genes, data analysis identified 11 cases with pathogenic variants (4 in BRCA1 and 7 in BRCA2) and 12 with uncertain variants (7 in BRCA1 and 5 in BRCA2). Only one case was found with a large BRCA1 deletion. Whole exome analysis allowed us to characterize pathogenic variants in additional causative genes and make the diagnosis in 21 individuals (11% diagnostic yield): 10 with pathogenic variants in genes more traditionally associated to breast and ovarian cancer (ATM, BRIP1, CDH1, PALB2, PTEN, RAD51C and TP53) and 11 in other cancer susceptibility genes (DPYD, ERBB3, ERCC2, MUTYH, NQO2, NTHL1, PARK2, RAD54L and RNASEL). In conclusion, this study allowed a personalized risk assessment and clinical surveillance in an increased number of HBOC families and to broaden the spectrum of causative variants also to “non-canonical” genes.